The shift to digital: designing for learning from a culturally relevant interactive media perspective - Engerman, Jason A.; Otto, Richard F. (Educational technology research and development, 2021)
In the midst of a global pandemic, higher education saw a modality shift to online learning that caused panic and discomfort as many instructors lacked the skills, resources, and didactic aptitude in this response (Lederman, The shift to remote learning: The human element. Retrieved from https://www.insidehighered.com/digital-learning/article/2020/03/25/how-shift-remote-learning-might-affect-students-instructors-and, 2020). The current review discusses the impact of this article for successful learning design as well as applications, limitations, constraints and future suggestions during the COVID-19 era. Specifically, this paper is in response to the article entitled, “The process of designing for learning: understanding university teachers’ design work” (Bennett et al., The process of designing for learning: Understanding university teachers’ design work. Educational Technology Research and Development, 65, 125–145. https://doi.org/10.1007/s11423-016-9469-y, 2017). The impact of the article under review can provide a roadmap to expert instruction with its focus on flexibility across interdisciplinary higher education fields of knowledge. In application, the findings of Bennett and her colleagues work, suggested designing for efficiency, broad considerations to specific details, and design and refining processes. The limitations of the current study under review, included having participants remember particular experiences of design with one-off interviews and no significant follow up. Given the aforementioned limitation, the next stage of research could be to develop a more explanatory and then prescriptive study to explore the rationale behind design decisions and strengthen implications. The descriptive framework of the current study allows educators and students opportunitiesto co-design authentic meaning making experiences given cultural relevant pedagogy. Ultimately, the current review concludes from a learning design perspective that focuses on culturally relevant educational ecosystems and interactive media.